A randomized controlled trial comparing primary retrograde intra renal surgery (RIRS) and extracorporeal shockwave lithotripsy (ESWL) for treatment of renal stones with suspected failure of ESWL in Hospital Tengku Ampuan Afzan (HTAA) - Aisah Munirah binti Wahi (Kulliyyah Medicine, International Islamic University Malaysia, 2016)
Incidence of urolithiasis in our country is 442 in 100,000 populations. Treatment modalities vary depending on the size and location of stone and patient's fitness for invasive treatment. Identifying the most suitable treatment modalities according to patient's clinical characteristic is important for efficacy of stone clearance with high safety profile and costly acceptable. We have prospectively conducted a randomized control trial comparing primary retrograde intrarenal surgery (RIRS) and extracorporeal shockwave lithotripsy (ESWL) for treatment of stone with suspected failure of ESWL in 74 patients. The demographic and clinical characteristics were determined using descriptive statistics. The comparison of stone clearance rate in between the groups was analyzed using Chi Square test. Stone clearance rate in primary RIRS group is higher (80.6%) compared to ESWL group (36.8%) and it is statistically significant (p<0.001). Stone clearance in ESWL group is significantly associated with smaller stone size (<1.0 cm), but no significant association of clearance to stone size in RIRS group. There is no significant association of stone clearance with stone location and body mass index (BMI) in these 2 groups. The complication rate is 19.4% in primary RIRS group and 18.4% in ESWL group.